Evaluation of seasonal dynamics and bioindication potential of macroalgal communities in a polluted tropical stream - Branco, LHZ; Pereira, J. L. (E Schweizerbart'sche Verlags, 2002)
Macroalgal communities and environmental variables were analyzed seasonally along a polluted tropical stream in São Paulo State, Brazil, We aimed to improve the knowledge of tropical macroalgal communities, to study the longitudinal and seasonal dynamics of these communities in influenced environments, to evaluate the relationship of algal frequency and abundance with selected environmental variables, and to look for potential macroalgal species indicators. The seasonal abundance pattern was similar to natural or low influenced systems and was mainly determined by rainfall regime. However, community composition was closely related to some chemical water pollution indicators, such as phosphorus and nitrogen compounds. Some species are suggested as potential indicators of organic pollution (e.g. Oscillatoria ornata, Stigeoclonium helveticum and Schizomeris leibleinii), but more detailed studies have to be developed to determine the tolerance limits of these species. on the basis of our results and literature data, the use of occurrence of Oscillatoriales in relation to other orders of Cyanoprokaryota is suggested to be a good indicator of organic pollution in tropical lotic ecosystems.
Keywords: algal frequency; macroalgal species indicators; organic pollution; Oscillatoriales; Cyanoprokaryota